Transnational Intellectual Property and Innovation Strategies: Evidence from China-U.S. Patent Dyads - HUANG, Kenneth Guang-Lih (Institutional Knowledge at Singapore Management University, 2012)
As firms increasingly operate and conduct R&D in emerging economies, “transnational patenting” – patenting of the same invention across more than one country – is becoming a cornerstone of their innovation strategy. We examine the impact of transnational patenting on technological knowledge formation and adoption using 4226 China-US patent dyads covering 1104 firms. Difference-in-differences estimates show that patent granted to an invention under a weak intellectual property right (IPR) institution (China) increases its subsequent knowledge adoption by up to 76% under a strong IPR institution (U.S.). The effect is most salient for patents awarded to China-based firms, in computing and information technology, and to firms located in Chinese municipalities with comprehensive IPR system. Innovation strategies employed in emerging markets could shape firms’ knowledge processes in developed markets.